Peran Guru dalam Pengembangan Kurikulum Merdeka - Rahmawati, Sri; Astuti, Devi; Fadriati, Fadriati (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Teachers have a strategic role as the spearhead of human resource development, so teachers play a role in developing the curriculum. Objectives This research explores the role of teachers in developing an independent curriculum. This research method uses a literature review. The main source of this research data is research articles published through google scholar in the last 10 years. Data collection was carried out using the keywords